Analysis of Social Studies Learning Media Needs in Economic Activity Materials in Elementary Schools - Noviawati, Yustin; Rachmadyanti, Putri; Ummah, Fiena Saadatul; Mariana, Neni (Journal of Learning Improvement and Lesson Study, 2025)
Social studies learning in elementary schools is often considered boring because the delivery of material tends to be conventional, focusing on lectures and memorization methods. This study aims to analyze the need for social studies learning media for the economic activities of fifth-grade students at SDN Simomulyo I Surabaya. This study used a qualitative descriptive approach with a needs analysis type. The research subjects consisted of fifth-grade teachers and fifth-grade students. Data collection techniques included observation, interviews, and questionnaires. The results showed that social studies learning is still conventional and teacher-centered. The media used has not been able to attract student interest, resulting in low learning motivation. Based on the results of the needs analysis, it was found that students need interactive, contextual, and educational game-based learning media. The economic monopoly game media is considered to have the most potential for development because it can simulate real economic activities, foster cooperation, and increase learning motivation.